2013
DOI: 10.1140/epjd/e2013-40153-y
|View full text |Cite
|
Sign up to set email alerts
|

Metastability exchange optical pumping of 3He gas up to hundreds of millibars at 4.7 Tesla

Abstract: Abstract. Metastability exchange optical pumping (MEOP) is experimentally investigated in3 He at 4.7 T, at room temperature and for gas pressures ranging from 1 to 267 mbar. The 2 3 S-2 3 P transition at 1083 nm is used for optical pumping and for detection of the laser-induced orientation of 3 He atoms in the rf discharge plasma. The collisional broadening rate is measured (12.0 ± 0.4 MHz mbar −1 FHWM) and taken into account for accurate absorption-based measurements of both nuclear polarization in the ground… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 28 publications
0
42
0
Order By: Relevance
“…The maximum rate is experienced by atoms in the velocity class v * that is resonant with the laser frequency, and is given by: γij(v,r)=2πafmnormaleωγ2γnormalΓ/2Ilas(r)Tijγ, where I las ( r ) is the laser intensity, ω its angular frequency, α the fine structure constant, f the oscillator strength of the transition, and m e the electron mass; the numerical value of the first fraction is 0.149 m 2 /W. The total damping rate of the optical coherence of the transition, Γ′/2 = γ + πw , results from the combined effects of the radiative decay rate γ and of the pressure-dependent collisional broadening w , with a value for w / p of order 20 MHz/mbar (Vrinceanu et al , 2004) or 12 MHz/mbar (Nikiel-Osuchowska et al , 2013) that remains to be confirmed. In the low-pressure limit ( w ≪ γ ), γ ij = T ij γ for I las = 6.7 W/m 2 .…”
Section: Metastability-exchange Optical Pumpingmentioning
confidence: 99%
See 4 more Smart Citations
“…The maximum rate is experienced by atoms in the velocity class v * that is resonant with the laser frequency, and is given by: γij(v,r)=2πafmnormaleωγ2γnormalΓ/2Ilas(r)Tijγ, where I las ( r ) is the laser intensity, ω its angular frequency, α the fine structure constant, f the oscillator strength of the transition, and m e the electron mass; the numerical value of the first fraction is 0.149 m 2 /W. The total damping rate of the optical coherence of the transition, Γ′/2 = γ + πw , results from the combined effects of the radiative decay rate γ and of the pressure-dependent collisional broadening w , with a value for w / p of order 20 MHz/mbar (Vrinceanu et al , 2004) or 12 MHz/mbar (Nikiel-Osuchowska et al , 2013) that remains to be confirmed. In the low-pressure limit ( w ≪ γ ), γ ij = T ij γ for I las = 6.7 W/m 2 .…”
Section: Metastability-exchange Optical Pumpingmentioning
confidence: 99%
“…The photon efficiency of these high-field optical pumping schemes can be as high as in low field ( η ≈ 1 for normalf2- pumping at high pressure) but this remains to be systematically studied (Batz et al , 2011; Nikiel-Osuchowska et al , 2013). With modified He level structures and only weak hyperfine couplings remaining in the excited states, high-field MEOP has two distinct features: highly absorbing lines can be used, with absorption coefficients ≃ 10 times larger than for C 8 or C 9 pumping at low field, and the transfer of angular momentum to the ground state is orders of magnitudes slower than in low field at a given pressure.…”
Section: Metastability-exchange Optical Pumpingmentioning
confidence: 99%
See 3 more Smart Citations